A study to assess the readiness of rice farmers to use agricultural technology for production in Nong Khai Province, Thailand - Panyasit, Kamoltip; Singhavara, Montri; Srihirun, Jenasama; Wangsathian, Supreeya; Nonthapot, Sakkarin (International Journal of Innovative Research and Scientific Studies, 2024)
This article aims to study the attitude factors affecting the intention to use agricultural technology in the production of rice by farmers in Nong Khai province through a technology acceptance model based on structural equation analysis. Nong Khai, one of the provinces located in Thailand’s north-eastern region, has the largest rice production area. The area is suited for agriculture due to its proximity to significant water sources, such as the Mekong River. In this research, data were collected from a group of rice farmers in Nong Khai Province to study the readiness of the sample group that affected the intention to use Amino-KP 2 instead of chemical fertilizer. It was found that there was the highest level of acceptance or intention to use an interpretation of the meaning. The results of all hypothesis testing showed that optimism and interest in innovation influence perceived usefulness and perceived ease of use. The perceived usefulness factor was hindered by the insecurity variable, while the perceived ease of use factor was unaffected. Additionally, the discomfort of using technology hindered the perceived ease of use factor, but the perceived usefulness remained unaffected. The perceived ease of use factor was also found to have a positive influence on the perception of usefulness. Perceived usefulness and perceived ease of use both had a positive influence on the intention to use Amino-KP 2.